The Evolution of Homo Ludens: Sexual Selection and a Theology of Play - Loumagne, Megan (Zygon, 2022)
This essay argues that reflection on sexual selection can be theologically generative, and that it presents needed counteremphases to some of the discussions about theological anthropology that have been fueled by theological reflection on natural selection. It introduces sexual selection and provides an overview of different approaches to sexual selection found within evolutionary biology today, before transitioning to a reflection on one theologically relevant insight from sexual selection—namely, the importance of play. It argues that the mating and play behaviors of animals reveal the noncompetitive relationship between necessity and gratuity, and thus provide theologians with an example of grace building upon, and not destroying, nature. While play is sometimes depicted in philosophical and theological accounts as the achievement of culture that supersedes the mundane necessities of nature, sexual selection can also help to illuminate the ways in which culture is dependent upon nature, and play is a thoroughly natural phenomenon that provides resources for human cultural elaboration.